Activism, alliance building, and the Esperanza Peace and Justice Center - DeTurk, Sara (Lexington Books, 2015)
This critical ethnography describes the context, vision, and social change tactics of the Esperanza Peace and Justice Center in San Antonio, Texas. It explicates the important roles of intergroup alliances, strategic use of language, and arts programming as a means of connecting personal consciousness-raising to collective agency.